Implementation Of C4.5 Algorithm For Predicting Late School Tuition Payments Using Python - Victor Saputra Ginting; Kusrini Kusrini; Emha Taufiq (STMIK AKBA, 2020)
The Donation of Educational Development (SPP) School is one of the important components in implementing education, because School SPP is one of the requirements in achieving educational goals. Research conducted by Muqorobin, 2019 with the title